2020
DOI: 10.21071/az.v69i268.5392
|View full text |Cite
|
Sign up to set email alerts
|

Caracterización técnica y económica del sistema de producción de búfalos Bubalus bubalis en el departamento de Córdoba de Colombia

Abstract: El objetivo de este trabajo fue realizar un estudio descriptivo que permitiera generar información básica tecnológica y socioeconómica de los sistemas de producción de búfalos en el departamento de Córdoba, Colombia. La recopilación de información se obtuvo por medio de un formulario de encuesta aplicada a 26 unidades productivas. Los indicadores estadísticos fueron tabulados y analizados con el programa SPSS. Se permite apreciar que el 63% de los sistemas de producción tienen una vocación de doble propósito d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
1
0
0
1
Order By: Relevance
“…In the case of males, 100% of the producers indicated that they are destined for meat production, and 35.7% of the producers consider that their males can be used as breeding stock. The results are similar to those reported in a study in Colombia, in which it was mentioned that the greater number of females is consistent with a sustainable herd from the technical point of view because it guarantees the continuity of production, while the males have a defined duration in the herd [17].…”
Section: Herd Inventorysupporting
confidence: 90%
“…In the case of males, 100% of the producers indicated that they are destined for meat production, and 35.7% of the producers consider that their males can be used as breeding stock. The results are similar to those reported in a study in Colombia, in which it was mentioned that the greater number of females is consistent with a sustainable herd from the technical point of view because it guarantees the continuity of production, while the males have a defined duration in the herd [17].…”
Section: Herd Inventorysupporting
confidence: 90%
“…Como complemento al ejercicio se hicieron los análisis comparativos para dos situaciones, una con tratamiento de enfermedades y una convencional con algunos tratamientos mínimos, la comparación se hizo con base en los retornos económicos estableciendo las diferencias en cada caso, las técnicas empleadas se basan en las aplicadas por Martinez (2020).…”
Section: Gastos Por Tratamientosunclassified